Allen Squires, his sister Delcie, Syl, and a Duke the dog. - Squires, Allen; Squires, Pearl (1962)
Photograph of three people and a dog in a garden. From left to right: Allen Squires, Delcie (Allen's sister), and Syl. Dogs name is Duke. Slide labels by Pearl Squires identifies individuals by first name only.